Recent Advances in Materials, Synthesis, and Reaction Model of Particle Adsorbent for Flue Gas Desulfurization - Yanni Xuan; Kun Yu; Hong Tian; Zhangmao Hu; Wei Zhang; Yanshan Yin; Haitao Gao; Qingbo Yu (Molecules)
Particle adsorbents have gained significant traction in flue gas desulfurization applications, primarily attributed to their high structural homogeneity and large specific surface area. To address the multifaceted requirements of industrial sectors regarding the structural configurations and physicochemical properties of particle adsorbents while promoting sustainable manufacturing practices, this study systematically evaluates and critically appraises contemporary advancements in particle desulfurizing agent technologies. The synthesis of these findings establishes a theoretical framework to facilitate technological innovation and industrial progress within the particle desulfurizer domain. The research systems of particle adsorbents, encompassing active components, inert carriers, preparation methodologies, and gas–solid reaction models, were comprehensively reviewed. The advantages and current limitations of these systems were then systematically summarized. Finally, the fundamental principles and research trajectories in the application fields of distinct particle adsorbent research systems were elucidated. An analysis of the developmental trends indicated that enhancing the utilization efficiency of active components and improving the cyclic stability of adsorbents remained critical engineering challenges. It is posited that the pursuit of high reaction activity, thermal stability, mechanical strength, and superior anti-aggregation/sintering performance constitutes key directions for the advancement of particle adsorbents in China’s flue gas desulfurization industry.